Pembuatan Busana Pesta Malam Dengan Sumber Ide Renaissance Italia Menggunakan Penerapan Smock Pada Corset Dan Hiasan Payet - Chalita Oktavianita Risqi; Arina Haq (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2024)
Making a party fashion design takes pouring creative ideas to create a fashion design. The source of the idea is an idea that comes out to create an innovative creation one of which can be taken from the renaissance. Smock is a technique of making wrinkles on the fabric symmetrically or asymmetrically. Smock used in this study is a wave smock. In making this final project the author raised the issue of how the application of the Italian renaissance ideas in the manufacture of fashion evening party, where women at this time wear clothes that have characteristics that show luxury, glamor, feminine, shiny, tight (press body), rigid and made fall. This writing aims to determine the process of making party dress with renaissance ideas source using the application of smock on corset and sequin decoration. The method of data collection used in this paper is the method of observation, documentation and lite The process of making clothes in this study starts from determining the design of clothing, sizing, making basic patterns to break patterns, making smock, laying patterns, cutting materials, and pattern marks. The initial stage in the process is sewing a translucent top, tanktop, corset and circle skirt. The conclusion of the process of making this dress is that the manufacture of smock is carried out with accuracy.Installation of the smock on the corset must also be done with the appropriate technique, so that the results look right. The suggestion in this report is that the smock making process must pay attention to the needs of the fabric, so that during the smock making process there is no shortage of materials. The process of installing the smock must be considered, because in this installation technique it determines the accuracy of the results attached to the corset.rature. The analysis used in this study is qualitative analysis.